Junie B., First Grader (At Last!) - Park, Barbara; Brunkus, Denise (New York : Random House, 2001)
Junie B. thinks first grade is a flop when her kindergarten friend Lucille prefers the company of twins Camille and Chenille and Junie B. needs glasses.
a"A Stepping stone book."
Keywords: Schools -- Fiction; Eyeglasses -- Fiction; Friendship -- Fiction